2004
DOI: 10.1007/s11249-004-8078-9
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry of Overbased Calcium Detergents Studied by ToF-SIMS and Other Surface Analyses

Abstract: Overbased detergents are well known in the tribology field as anti-wear additives. In boundary lubrication, they generate a quite thick tribofilm on rubbing surfaces. They were studied by coupling XPS and AES depth profiles with XANES and ToF-SIMS analyses. Under friction, we show by ToF-SIMS analysis that detergent molecules are split into smaller structural units. Moreover, ionic bonds do not resist high pressure and shearing, and sulfur disappears from the contact zone. The overbased calcium carbonate core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
(11 reference statements)
0
24
0
Order By: Relevance
“…These include X-ray scattering [17], reflection infrared spectroscopy [18], XPS [10], TOF-SIMS [19,20] and XANES [16]. Most studies have identified a solid-like films of CaCO 3 in the form of calcite.…”
Section: Introductionmentioning
confidence: 99%
“…These include X-ray scattering [17], reflection infrared spectroscopy [18], XPS [10], TOF-SIMS [19,20] and XANES [16]. Most studies have identified a solid-like films of CaCO 3 in the form of calcite.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work on working mechanism on overbased sulfonates [13], we have found that calcium oxide deposited on rubbing surface plays an important role on reduction of friction and wear. Kinetics of the film formation, especially decomposition of micelle structure of the over-based sulfonate to disclose the inorganic moiety has been investigated by Time-of-flight secondary mass spectroscopy (TOF-SIMS) analysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this deposited film is analogous to the films deposited by traditional phosphorous and sulfur containing antiwear additives like ZDDP. These films have been analyzed by a variety of techniques (ToF-SIMS [9], XRD [10], EELS [11], XPS [12], and XANES [13]) to determine their chemical and structural composition on a rubbed metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…The tribofilms formed in the Cameron-Plint tribometer were studied using XPS which indicated that the calcium sulfonate chains were expelled during rubbing, while the CaCO 3 core crystallized on the metal surface. Additionally, it was conjectured that part of the CaCO 3 decomposed to CaO and CO 2 after deposition on the surface (although the mechanism is still unclear) [9].…”
Section: Introductionmentioning
confidence: 99%